First Acyclic Diene Metathesis Polymerization Under Biphasic Conditions Using a Dicationic Ruthenium Alkylidene: Access to High‐Molecular‐Weight Polymers with Very Low Ruthenium Contamination. Issue 2 (19th September 2014) - Zhao, Jing; Wang, Dongren; Autenrieth, Benjamin; Buchmeiser, Michael R.; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> The acyclic diene metathesis (ADMET) polymerization of 6‐hydroxy‐1, 10‐undecadiene (M1) and 6‐acetoxy‐1, 10‐undecadiene (M2) by the action of two different catalysts, i.e., the second‐generation Grubbs‐Hoveyda system ([RuCl2(IMesH2)(CH‐2‐(2‐PrO‐C6H4)]) (1) and the dicationic ruthenium alkylidene [Ru(DMF)3(IMesH2)(CH‐2‐(2‐PrO‐C6H4)] (2, IMesH2 = 1, 3‐dimesitylimidazolin‐2‐ylidene) is reported. Biphasic conditions using 1‐butyl‐2, 3‐dimethylimidazolium tetrafluoroborate ([BDMIM+BF4−]) and 1, 2, 4‐trichlorobenzene (TCB) are applied. Under the chosen conditions (T = 75 °C, 20 mbar), the use of catalyst 1 results only in the formation of low‐molecular‐weight polymers (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh372v5r1c" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M¯n</alternatives> ≤ 10 000 g mol−1), while catalyst 2 allows for the high yield synthesis of high‐molecular‐weight polymers (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh372v5r64" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M¯n</alternatives> ≤ 40 000 g mol−1, yields ≤ 99%). Irrespective of the catalyst used, all polymers display a high trans‐content (>95%). Notably, Ru‐contamination of the target polymers without any additional purification is as low as 1.2 ppm with catalyst 2. Together with the high yields and high molecular weights, the low Ru‐contaminations clearly illustrate the advantages of the biphasic setup. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>